1990
DOI: 10.1161/01.str.21.11.1545
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience with cerebral amyloid angiopathy.

Abstract: Cerebral amyloid angiopathy can present as lobar intracerebral hemorrhage in an elderly person, presumably due to increased fragility of the vessels affected by amyloid deposition. For this reason, patients presenting with intracerebral hemorrhage and suspected of having cerebral amyloid angiopathy have often been treated nonsurgically. Since 1983 we have evaluated 11 patients with cerebral amyloid angiopathy (nine women and two men, mean age 73 years) who have undergone either intracerebral hematoma evacuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…14,19,24,29,36,56,113,119 The prevalence of hypertension in those patients is significantly lower than that found in the general population 65-74 years old. 52 In studies reporting estimated hematoma volume, the average volume was 57 cm 3 .…”
Section: Literature Review Of Surgical Case Seriesmentioning
confidence: 90%
See 1 more Smart Citation
“…14,19,24,29,36,56,113,119 The prevalence of hypertension in those patients is significantly lower than that found in the general population 65-74 years old. 52 In studies reporting estimated hematoma volume, the average volume was 57 cm 3 .…”
Section: Literature Review Of Surgical Case Seriesmentioning
confidence: 90%
“…14,35,41,78 However, since those early reports, there have been numerous surgical series reporting safe performance of hematoma evacuation and cortical biopsy (Table 4). 16,19,24,29,33,49,56,97 Many of these case series specifically state that the authors experienced no problems with intraoperative hemostasis. 29,49,56,68 The establishment of surgical safety in CAA is extremely important when discussing minimally invasive techniques where hemostasis can be more cumbersome to attain.…”
Section: Surgical Management Of Amyloid-associated Ichmentioning
confidence: 99%
“…39,40 Several reports have also referred to the safety of the biopsy of the cerebral cortex in patients with CAA-ICH. [41][42][43][44] Mehndiratta et al reported that the probability of postoperative hemorrhage within the first 48 hours of surgery was 11.8% on average (the probability ranged from 0% to 22% among the previous reports), and the mortality rate was 24.4% on average (0%-75%) in patients with CAA-ICH. The patients' poor outcome in CAA-ICH with surgical intervention was estimated to be associated with poor preoperative functional status, age over 75 years, preoperative diagnosis of dementia, hematoma volume greater than 60 ml, the presence of IVH, and postoperative hemorrhage.…”
Section: Safety Of Craniotomy and Biopsy In Patients With Caa-ichmentioning
confidence: 98%
“…2 The clinical risk profile in CAAH has not, however, been firmly established. 5 Although previous reports of CAAH have included patients who were taking antiplatelet or anticoagulant medication, 6 -8 had suffered minor head trauma 9 or had hypertension, 10 it is unclear whether these clinical features are risk factors for CAAH that are independent of the effects of APOE genotype. In the present study we have established the frequency of these putative clinical risk factors in a large series of patients with a pathological diagnosis of CAAH and compared our findings with those in previous reports.…”
mentioning
confidence: 99%